РОЛЬ ГОСУДАРСТВА В ПОВЫШЕНИИ СОЦИАЛЬНОЙ ОТВЕТСТВЕННОСТИ ЛЕСОПРОМЫШЛЕННОГО КОМПЛЕКСА - Воронин, Анатолий; Рудаков, Михаил; Шегельман, Илья (Федеральное государственное автономное образовательное учреждение высшего профессионального образования «Северный (Арктический) федеральный университет им. М.В. Ломоносова», 2007)
The article analyses urgent problems of timber industry complex social responsibility in the North-west Federal district and the Republic of Karelia in coordination with the development of economy and consolidation of budgets. Purposeful change of relations between subjects of forest management and state authorities is considered to be the most important way of solving problems in the timber industry complex.